Analisis Yuridis terhadap Eksistensi Anggota Dewan Perwakilan Daerah (DPD) RI - Teguh Wicaksono (Pusat Riset dan Inovasi Nasional, 2023)
The existence of the DPD as one of the representative institutions at the central level, to date, its duties and authority as well as its functions are unclear and do not have a clear impact on the institutions it represents. This is different from the DPR, which is explicitly stated in the 1945 Constitution of the Republic of Indonesia, for example regarding its supervisory function, budget function and legislative function, which makes the DPR able to exist in parliament. Thus, an in-depth study is needed to confirm the position and function of the DPD so that it is not just an institution that spends a lot of its budget on salaries but whose performance is unclear and does not provide any insight into the institution or electoral district where the members come from. In this research, input was obtained, namely to revise the 1945 Constitution of the Republic of Indonesia to strengthen the function of the DPD or remove the DPD from state institutions because it is no longer effective.